Micropapillary Adenocarcinoma of the lung: Recent updates and literature review - Paloma del C Monroig-Bosque; Ahmed N Shehabeldin; Jae Y Ro (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2019)
Background: Lung cancer is the most frequent cause of cancer-related death worldwide. For adenocarcinomas, histological subtyping is typically performed (e.g. lepidic, acinar, papillary, micropapillary, and solid), as suggested by the World Health Organization. Among these, micropapillary carcinoma has been a focus of significant research in recent years, as it is the newest subtype and has the worst prognosis. Herein, we summarize the most relevant findings of this morphological variant in detail with anecdotal experience and a review of the published literature. Results: A PubMed query for "adenocarcinoma of the lung" resulted in 177 full-length articles. The reviewed articles were grouped by category as follows: 1) history (2002-2008), 2) morphologic/diagnostic features, 3) prognostic implications, 4) molecular features and targeted therapies, and 5) radiologic/imaging findings. Our results consistently showed that a micropapillary carcinoma component is associated with poor prognosis in patients with lung adenocarcinoma. Additionally, our investigation highlighted the fact that there have been no studies validating the diagnostic/morphologic criteria that should be used to achieve an accurate diagnosis of micropapillary lung adenocarcinoma. Nonetheless, we present that molecular studies continue to emerge, and there is significant opportunity for targeted therapeutic options that remains to be explored in depth.  Conclusion: Our review offers insight into novel studies focused on micropapillary lung adenocarcinoma. We present the potential for new research opportunities, particularly molecular studies aimed at determining targeted treatment options.